2003
DOI: 10.1007/s10194-003-0051-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity of NOS, CGRP, PACAP, SP and VIP in the trigeminal nucleus caudalis and in the cervical spinal cord C1 and C2 of the cat

Abstract: IntroductionNeurovascular headaches, such as migraine and cluster headache, are very disabling, common disorders. Despite much progress in research during recent years both at the therapeutic level with the development of triptans and at the level of the general understanding of the basic mechanisms, there is still much to learn about these disorders [1].Nociceptive fibers on intracranial vessels such as the superior sagittal sinus (SSS) and the middle meningeal and middle cerebral arteries [2] are central in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…CGRP positive fibers were found in laminae I and II. Similar staining pattern has been demonstrated previously in the chick, quail dorsal horn of the spinal cord [31] and in the cat [32]. In addition, we observed some CGRP positive neurons and fibers close to the central canal (laminae X).…”
Section: Discussionsupporting
confidence: 89%
“…CGRP positive fibers were found in laminae I and II. Similar staining pattern has been demonstrated previously in the chick, quail dorsal horn of the spinal cord [31] and in the cat [32]. In addition, we observed some CGRP positive neurons and fibers close to the central canal (laminae X).…”
Section: Discussionsupporting
confidence: 89%
“…A marked increase of the immediate early gene c-fos in laminae I and II of the TNC and in the superficial layers of the C1 and C2 regions can be seen upon stimulation of the middle meningeal artery, the superior sagittal sinus or the trigeminal ganglion in monkeys and cats [80,101,115]. However, the expression of neuropeptides in the brainstem is unaltered during 2 hours of superior sagittal sinus stimulation [27]. The c-fos response is reduced by anti-migraine drugs, such as triptans [116,118].…”
Section: ) What Is the Role Of The Trigeminocervical Complexs?mentioning
confidence: 91%
“…there is a moderate supply of CGRP and PACAP fibres in these areas while NOS or VIP fibres were not seen [27].…”
Section: ) What Is the Role Of The Trigeminocervical Complexs?mentioning
confidence: 99%
“…Tracing studies have revealed that VIP‐positive nerves originate in the sphenopalatine and otic ganglia, while PACAP‐positive neurons are found both in the above parasympathetic ganglia, but also in the human trigeminal ganglion, where there is no VIP immunoreactivity . The localization of PACAP to both parasympathetic and sensory systems would suggest that, unlike VIP, the role of this peptide is dual on vasomotor function and sensory mechanisms . This could explain that PACAP infusion into migraineurs triggers migraine and indeed produces vasodilatation and, occasionally, headache in nonmigraine subjects, while VIP, a more potent cranial vasodilator, does not induce such headache …”
Section: Commentsmentioning
confidence: 99%
“…36 The localization of PACAP to both parasympathetic and sensory systems would suggest that, unlike VIP, the role of this peptide is dual on vasomotor function and sensory mechanisms. [37][38][39] This could explain that PACAP infusion into migraineurs triggers migraine 21 and indeed produces vasodilatation 40 and, occasionally, headache in nonmigraine subjects, while VIP, a more potent cranial vasodilator, does not induce such headache. 41 This study has some limitations.…”
Section: Commentsmentioning
confidence: 99%